Cost-benefit studies of natural resource management in southeast Asia - James, David; Francisco, Herminia A. (Singapore Springer, 2015)
Contents: guide to cost-benefit analysis and case studies; agriculture, forestry and fisheries; river basin management; protected areas; adaptation to climate change,...
Keywords: Kỹ thuật môi trường